(untitled) (SCIENCE TIME JOURNAL, 2026)
Writing is considered one of the most challenging language skills for learners of English as a Foreign Language (EFL). Unlike speaking or listening, writing requires learners to demonstrate grammatical accuracy, lexical competence, coherence, organization, and critical thinking simultaneously. This study investigates the common difficulties experienced by EFL learners in academic writing and examines the linguistic, cognitive, and pedagogical factors contributing to these challenges. The paper adopts a qualitative analytical approach based on previous empirical studies, classroom observations, and theoretical discussions in the field of second language acquisition. The findings reveal that EFL learners commonly struggle with grammar, vocabulary selection, sentence structure, cohesion, coherence, punctuation, and idea organization. Psychological factors such as writing anxiety, lack of confidence, and limited exposure to authentic English texts also significantly affect learners’ performance. Furthermore, inadequate teaching strategies and insufficient feedback mechanisms often intensify writing problems. The study emphasizes the importance of process-oriented writing instruction, continuous practice, corrective feedback, and learner-centered pedagogical approaches in improving writing proficiency.